Interleukin 10-coated nanoparticle systems compared for molecular imaging of atherosclerotic lesions - Almer G (Dove Medical Press, 2014)
Gunter Almer,1,* Kelli L Summers,1,2,* Bernhard Scheicher,2 Josef Kellner,3 Ingeborg Stelzer,1 Gerd Leitinger,4,5 Anna Gries,3 Ruth Prassl,6 Andreas Zimmer,2 Harald Mangge1,7 1Clinical Institute of Medical and Chemical Laboratory Diagnostics, Medical University of Graz, Graz, Austria; 2Institute of Pharmaceutical Sciences, Department of Pharmaceutical Technology, University of Graz, Graz, Austria; 3Institute of Physiological Chemistry, Medical University of Graz, Graz, Austria; 4Research Unit Electron Microscopic Techniques, Institute of Cell Biology, Histology and Embryology, Medical University of Graz, Graz, Austria; 5Center for Medical Research (ZMF), Medical University of Graz, Graz, Austria; 6Institute of Biophysics, Medical University of Graz, Graz, Austria; 7BioTechMed, Graz, Austria*These authors contributed equally to the study Abstract: Atherosclerosis (AS) is one of the leading causes of mortality in high-income countries. Early diagnosis of vulnerable atherosclerotic lesions is one of the biggest challenges currently facing cardiovascular medicine. The present study focuses on developing targeted nanoparticles (NPs) in order to improve the detection of vulnerable atherosclerotic-plaques. Various biomarkers involved in the pathogenesis of atherosclerotic-plaques have been identified and one of these promising candidates for diagnostic targeting is interleukin 10 (IL10). IL10 has been shown to be a key anti-inflammatory responding cytokine in the early stages of atherogenesis, and has already been used for therapeutic interventions in humans and mice. IL10, the targeting sequence, was coupled to two different types of NPs: protamine-oligonucleotide NPs (proticles) and sterically stabilized liposomes in order to address the question of whether the recognition and detection of atherosclerotic-lesions is primarily determined by the targeting sequence itself, or whether it depends on the NP carrier system to which the biomarker is coupled. Each IL10-targeted NP was assessed based on its sensitivity and selectivity toward characterizing atherosclerotic-plaque lesions using an apolipoprotein E-deficient mouse as the model of atherosclerosis. Aortas from apolipoprotein E-deficient mice fed a high fat diet, were stained with either fluorescence-labeled IL10 or IL10-coupled NPs. Ex vivo imaging was performed using confocal laser-scanning microscopy. We found that IL10-targeted proticles generated a stronger signal by accumulating at the surface of atherosclerotic-plaques, while IL10-targeted, sterically stabilized liposomes showed a staining pattern deeper in the plaque compared to the fluorescence-labeled IL10 alone. Our results point to a promising route for enhanced in vivo imaging using IL10-targeted NPs. NPs allow a higher payload of signal emitting molecules to be delivered to the atherosclerotic-plaques, thus improving signal detection. Importantly, this allows for the opportunity to visualize different areas within the plaque scenario, depending on the nature of the applied nanocarrier.Keywords: interleukin 10, atherosclerotic plaques, nanoparticles, proticles, liposomes